Disentangling the role of the Y(4260) in e+e−→D⁎D¯⁎ and Ds⁎D¯s⁎ via line shape studies - Si-Run Xue; Hao-Jie Jing; Feng-Kun Guo; Qiang Zhao (Physics Letters B, 2018)
Whether the Y(4260) can couple to open charm channels has been a crucial issue for understanding its nature. The available experimental data suggest that the cross section line shapes of exclusive processes in e+e− annihilations have nontrivial structures around the mass region of the Y(4260). As part of a series of studies of the Y(4260) as mainly a D¯D1(2420)+c.c. molecular state, we show that the partial widths of the Y(4260) to the two-body open charm channels of e+e−→D⁎D¯⁎ and Ds⁎D¯s⁎ are much smaller than that to D¯D⁎π+c.c.. The line shapes measured by the Belle Collaboration for these two channels can be well described by the vector charmonium states ψ(4040), ψ(4160) and ψ(4415) together with the Y(4260). It turns out that the interference of the Y(4260) with the other charmonia produces a dip around 4.22 GeV in the e+e−→D⁎D¯⁎ cross section line shape. The data also show an evidence for the strong coupling of the Y(4260) to the DD¯1(2420), in line with the expectation in the hadronic molecular scenario for the Y(4260).